Effect of dietary fat saturation on acylcoenzyme A: cholesterol acyltransferase activity of Ehrlich cell microsomes - D E Brenneman (Journal of Lipid Research, 1977)
Ehrlich cells grown in mice fed coconut oil diets (highly saturated) contain about twice as much cholesteryl ester as those grown in mice fed sunflower oil diets (highly polyunsaturated). Acylcoenzyme A: cholesterol acyltransferase (ACAT) activity was 30–100% higher in microsomes prepared from the cells grown on coconut oil (Mc) than in those prepared from the cells grown on sunflower oil (Ms). Increased ACAT activity was noted in Mc with either [1-14C]palmitoyl CoA or [1,2-3H]cholesterol as the labeled substrate. This occurred at all acyl CoA concentrations tested and, in the [1,2-3H]cholesterol assay, with palmitoyl, oleoyl, or linoleoyl CoA as the substrate. The pH optimum for ACAT activity was the same with Mc and Ms, pH 7.0. ACAT activity obeyed Michaelis–Menten kinetics at palmitoyl CoA concentrations between 1 and 10 µM. Substrate inhibition occurred at higher concentrations. Kinetic analysis with [1-14C]palmitoyl CoA as the substrate indicated that the apparent Km for Mc was 33% smaller than for Ms. There was no difference, however, in apparent Vmax values. The cholesterol and phospholipid contents of Mc and Ms were similar, but their fatty acid compositions differed considerably. Mc contained 2.7 times more monoenoic fatty acid and only half as much polyenoic fatty acid as Ms. Our results indicate that dietary modification of the microsomal fatty acid composition is associated with alterations in the activity of ACAT, an enzyme that is tightly bound to the microsomes. These changes in ACAT activity may be partly responsible for the differences in cholesteryl ester contents of Ehrlich cells grown in mice fed the coconut and sunflower oil diets.